The Impact of Parliamentary Threshold on Non-Parliamentary Parties in the 2024 General Election from the Perspective of Fiqh Siyasah - Rinaldi Gunawan; Syaddan Dintara Lubis (Dinasti Research, 2025)
This study examines the impact of the parliamentary threshold on non-parliamentary parties in the 2024 General Election through the lens of fiqh siyasah, an Islamic legal perspective on politics and governance. The study explores how the threshold policy affects the political participation, electoral strategy, and sustainability of non-parliamentary parties in Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews with political figures, content analysis of policy documents, and direct observations of campaign activities. The findings reveal that the parliamentary threshold poses significant challenges for non-parliamentary parties, limiting their representation and political influence. However, from the perspective of fiqh siyasah, these parties adopt strategic measures such as coalition-building, grassroots mobilization, and issue-based campaigns to remain politically relevant. The study concludes that the parliamentary threshold, while intended to stabilize governance, also raises concerns regarding political inclusivity and representation. In the framework of fiqh siyasah, an equitable political system should ensure fair opportunities for all political entities to contribute to democratic governance and public welfare